Different extraction pretreatments significantly change the flavonoid contents of Scutellaria baicalensis - Yu, Chunhao (2013)
CONTEXT: Scutellaria baicalensis is one of the most commonly used medicinal herbs, especially in traditional Chinese medicine. However, compared to many pharmacological studies of this botanical, much less attention has been paid to the quality control of the herb’s pretreatment prior to extract preparation, an issue that may affect therapeutic outcomes. OBJECTIVE: The current study was designed to evaluate whether different pretreatment conditions change the contents of its four major flavonoids in the herb, i.e., two glycosides (baicalin and wogonoside) and two aglycons (baicalein and wogonin). MATERIALS AND METHODS: An HPLC assay was used to quantify the contents of these four flavonoids. The composition changes of four flavonoids by different pretreatment conditions including solvent, treatment time, temperature, pH value, and herb/solvent ratio were evaluated. RESULTS: After selection of the first order time-curve kinetics, our data showed that at 50°C, 1:5 herb/water (in w/v) ratio and pH 6.67 yielded an optimal conversion rate from flavonoid glycosides to their aglycons. In this optimized condition, the contents of baicalin and wogonoside were decreased to 1/70 and 1/13, while baicalein and wogonin were increased 3.5 and 3.1 folds, respectively, compared to untreated herb. DISCUSSION AND CONCLUSION: The markedly variable conversion rates by different pretreatment conditions complicated the quality control of this herb, mainly due to the high amount of endogenous enzymes of S. baicalensis. Optimal pretreatment conditions obtained from this study could be used obtain the highest level of desired constituents to achieve better pharmacological effects.